Pancreatoduodenal resection in the treatment of complicated forms chronic pancreatitis - N. N. Veligotsky; S. E. Arutyunov; M. V. Klymenko; A. N. Veligotsky (Сучасні медичні технології)
Purposeof thestudy. Development ofindications for performing pancreatoduodenal resection in complicated forms of chronic pancreatitis.